2011
DOI: 10.2165/11594010-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Ipilimumab

Abstract: Ipilimumab (Yervoy®) is an anti-cytotoxic T-lymphocyte antigen (CTLA)-4 monoclonal antibody that has been approved in the US for the first- or second-line treatment of patients with malignant melanoma. In the EU, it is awaiting approval as second-line therapy for melanoma. Ipilimumab blocks the effects of the negative T-cell regulator CTLA-4, which may in turn augment T-cell responses to tumour cells. Preclinical studies have indicated that antibody blocking of CTLA-4 can lead to potent immune responses. Ipili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(86 citation statements)
references
References 3 publications
0
72
0
1
Order By: Relevance
“…This including vemurafenib (a B-Raf enzyme inhibitor also known as PLX4032) [41] and ipilimumab (a fully human antibody that binds to cytotoxic T lymphocyte-associated inhibitor, which may in turn augment T-cell responses to melanoma cells) [42]. B-Raf knockdown leads to apoptosis in the melanoma cell line A375 [43], however it did not come up as the best option on the basis of our preliminary in vitro studies (see under Results).…”
Section: Discussionmentioning
confidence: 99%
“…This including vemurafenib (a B-Raf enzyme inhibitor also known as PLX4032) [41] and ipilimumab (a fully human antibody that binds to cytotoxic T lymphocyte-associated inhibitor, which may in turn augment T-cell responses to melanoma cells) [42]. B-Raf knockdown leads to apoptosis in the melanoma cell line A375 [43], however it did not come up as the best option on the basis of our preliminary in vitro studies (see under Results).…”
Section: Discussionmentioning
confidence: 99%
“…The first anti-CTLA4 human monoclonal antibody (mAb), ipilimumab, was approved in 2011 by the FDA for use in metastatic melanoma (12). Following activity in phase II clinical trials, success for ipilimumab was reported in a large phase III clinical trial involving treatment of 676 patients with metastatic melanoma, who had undergone previous failed treatment (13).…”
Section: Negative Checkpoint Regulators New and Oldmentioning
confidence: 99%
“…Each MEDI1873 monomer comprises three distinct domains (Fig. 1A): 1 a human immunoglobulin G1 (IgG1) fragment crystallizable (Fc) domain, 2 an isoleucine zipper trimerization domain from human coronin 1A, 3 and the hGITRL extracellular domain (ECD), with a point mutation (N161D) that eliminates the sole occupied glycosylation site. We demonstrate that MEDI1873 can be purified to homogeneity and is a significantly more potent agonist of hGITR than a monoclonal antibody.…”
Section: Introductionmentioning
confidence: 99%